Some error occured while loading page for you. Please try again.
Sort 3 Discussions, By:
Please Login in order to post a comment
I was enjoying learning Haskell until now.
At the end I am left with (λz.w). While I know that it is true that this maps any z to w, why is it legal to write w instead of (λz.w)? w is a reference wheras (λz.w) is a function.
Hi, your formula derivation isn't right.
((λz.w) (λz.w)) = [(λz.w)/z]w = w
[(λz.w)/z]w = w The Right Sort of Tokens
Up to ((λz.w) (λz.w)), everything is fine. Now (λz.w) is the argument to be substituted for 0 occurrences of z in w; so the result of substitution will be w itself.
another learning use w or W has difference in test case
No more comments